Systemic Risk Assessment of the Capital Market: Based on the Decomposition of Oil Shock Effects in the SVAR-Copula-GARCH Framework - Rezaee, Neda; Chaharmahali, Shahram; Kohandel, Mohammad; Nourollahzade, Nowrouz (Management Strategies and Engineering Sciences, 2025)
The specific oil shocks also exhibited the lowest Akaike criterion values under a normal distribution. Analyzing the results of the copula model under the Student’s t-distribution revealed that significant risk spillovers exist between the two markets during all three types of shocks. However, regarding oil supply shocks, the results confirm the presence of spillover effects from oil supply shocks to the stock market, and the 95% Value at Risk (VaR) is higher than the corresponding conditional CoVaR at the same probability level. This indicates that risk spillover from the oil market supply is associated with lower levels of value at risk in the stock market. Regarding demand-side shocks and specific oil shocks, it was also observed that significant and asymmetric risk spillover effects from the oil market to stock returns are statistically significant and confirmable. The Expected Shortfall (ES) results, except for supply shocks, were consistent with the conditional Value at Risk calculations. In fact, for all three types of oil supply shocks, the ES value is higher at the 95% level, but at the 5% level, the conditional expected shortfall is greater. This, despite confirming the existence of risk spillover effects, suggests that the spillover of oil supply shocks to the stock market is not symmetric. The spillover effects have varied across different levels of market risk exposure, indicating a long-term interpretation of shock spillover effects. Additionally, increasing and decreasing values of supply shocks have not had the same impact on stock returns.